NR4A2 attenuates early brain injury after intracerebral hemorrhage by promoting M2 microglial polarization via TLR4/TRAF6/NF-κB pathway inhibition - Di Hu; Cheng Huang; Ling Tang; Jiawen Lei; Jiaqi Wang; Wenzheng Hu; Minshan Chen; Siyuan Song; Lin Lu; Pingyi Xu (Cellular and Molecular Life Sciences)
Abstract In the early stage of intracerebral hemorrhage (ICH), rebleeding occurs when blood from the initial hematoma permeates the surrounding brain parenchyma through the disrupted blood–brain barrier (BBB), exacerbating brain injury. Neuroinflammation is a critical driver of the pathological processes underlying this phenomenon. Research on microglia near early hematomas revealed that promoting the transition of microglia to the M2 phenotype could mitigate perihematomal inflammatory damage. Recent studies have shown that the nuclear receptor-related 1 protein (NR4A2) can regulate microglial function and inhibit inflammation. However, the functions of NR4A2 in the development of ICH are still unclear. In this study, we explored the potential protective effect and mechanism of NR4A2 in ICH models. Our results demonstrated that the expression of NR4A2 was significantly decreased in both ICH rats and cell models. Increasing NR4A2 activity could effectively decrease the hematoma volume, improve the neurological prognosis and alleviate perihematomal BBB damage. In vivo and in vitro experiments revealed that NR4A2 inhibited perihematomal inflammatory damage by driving microglial polarization toward the anti-inflammatory M2 phenotype. Mechanistically, NR4A2 targeted TLR4 and inhibited the TRAF6/NF-κB pathway, thereby promoting M2 microglial polarization, reducing inflammatory cell extravasation and maintaining the integrity of the BBB. Conversely, the protective effects of NR4A2 were negated when CRX-527 (a TLR4 agonist) was introduced. These findings suggest that NR4A2 represents a promising therapeutic target for ICH. Graphical abstract